SIKAP, MOTIVASI, DAN MINAT BERWIRAUSAHA MAHASISWA (Jurnal Manajemen dan Kewirausahaan, 2015)
The research was conducted at the Public Polytechnic of Kupang. The purpose of this study included getting overview of student interest in running entrepreneurship. The formulation of the problem was whether attitudes and motivation fostered entrepreneurial interest of students. The research method was simple random sampling (random) survey with quantitative analysis approach. Data was collected with questionnaires. Data was processed with SPSS. The research was used multiple linear regression. The results of this study indicated that the variable attitude and motivation no significant effect on the interest in entrepreneurship.